2021
DOI: 10.33910/2687-153x-2021-2-3-101-109
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and properties of polycrystalline PZT films obtained by RF magnetron sputtering with fine variation of the composition near morphotropic phase boundary

Abstract: The article discusses the possibilities of fine composition variation of polycrystalline PZT films at the morphotropic phase boundary. The composition of thin films prepared by RF magnetron sputtering of a ceramic target of stoichiometric composition PbZr 0.54 Ti 0.46 O 3 was varied by changing the distance from the target to the substrate in the range of 30-70 mm. This made it possible to change the composition by ~1.5%. The study focused on the dielectric properties of the formed self-polarized films. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
0
0
2
Order By: Relevance
“…The absence of splitting may be due to the fact that the reflexes were extensively widened. The most probable cause of such widening is nonuniform distribution of Ti and Zr atoms over the thickness, which, as estimated, reached ∼ 3% [26,27].…”
Section: Experimental Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of splitting may be due to the fact that the reflexes were extensively widened. The most probable cause of such widening is nonuniform distribution of Ti and Zr atoms over the thickness, which, as estimated, reached ∼ 3% [26,27].…”
Section: Experimental Findings and Discussionmentioning
confidence: 99%
“…For the purpose of this study, PZT thin films were deposited by radio-frequency magnetron deposition of ce- [26,27]. Such variations of complex film composition were associated with the thermalization length difference in gas plasma of atoms which differ in their weight [28,29].…”
Section: Specimen Preparation and Study Methodsmentioning
confidence: 99%
“…The relevance of these studies is evidenced, however, by the fact that in thin PZT films in a narrow region of the morphotropic phase boundary (MPB), anomalously high electromechanical and piezoelectric parameters are observed, and it is obvious that a change in the microstructure of films can most decisively affect their physical characteristics. We carried out the first studies in this direction in previous years and found anomalous changes in the signal of the second optical harmonic (Elshin et al 2020) and changes in the dielectric characteristics (Dolgintsev et al 2021). The purpose of this work was to elucidate the possible causes of such anomalies in thin films of PZT.…”
Section: Spherulitic Microstructure Of Thin Pzt Filmsmentioning
confidence: 95%
“…Изменением расстояния мишень-подложка удавалось тонко варьировать состав (элементное соотношение атомов Ti и Zr) осажденных пленок в диапазоне Ti/Zr ∼ 48.5/51.5−47.0/53.0, то есть на 1.5%, рис. 2 [26,27]. Подобные вариации состава пленок сложного состава связаны с различием длин термализации в газовой плазме атомов, различающихся весом [28,29].…”
Section: приготовление образцов и методы исследованияunclassified
“…Отсутствие расщепления может быть связано с тем, что сами по себе рефлексы сильно уширены. Наиболее вероятной причиной такого уширения является неоднородность в распределении атомов Ti и Zr по толщине, оценочно достигающая ∼ 3% [26,27]. Зависимости характеризуются наличием скачка в области МФГ, при этом сами значения диэлектрической проницаемости остаются достаточно высокими для тонких пленок (∼ 600−800 для ε и ∼ 800−1200 для ε max ).…”
Section: экспериментальные результаты и их обсуждениеunclassified